Heart Failure with Atrial Fibrillation: Physical Domain Severely Compromised Despite Preserved Mental Well-Being - Indrawan Sani, Riyanda; Handayani, Ahmad; Annisa; Sheila Dhiene Putri (Ahmad Dahlan Medical Journal, 2025)
Atrial fibrillation (AF) frequently coexists with chronic heart failure (CHF), imposing a “double chronic burden” that may severely affect patients’ quality of life (QoL). This study aimed to evaluate QoL in CHF patients with AF using the SF-36 questionnaire, focusing on the most impaired physical and mental domains. A descriptive study was conducted on 30 adult patients (≥40 years) attending the Cardiology Clinic of Mitra Medika Amplas Hospital, Medan. QoL was assessed using the validated Indonesian version of SF-36, and data were analyzed descriptively. The mean age was 62 years, with 70% female, 76.7% having non-valvular AF, and common comorbidities including coronary artery disease (43.3%) and hypertension (33.3%). Physical domains were severely impaired, with role physical (24.17), general health (37.00), and physical functioning (44.00), resulting in a low Physical Component Summary (PCS) of 30.0. In contrast, mental domains were relatively preserved, with mental health (80.93), vitality (80.17), and social functioning (76.35), yielding a Mental Component Summary (MCS) of 57.5. These findings indicate that CHF patients with AF experience substantial physical limitations despite maintained mental well-being, highlighting the importance of interventions targeting physical function while supporting psychosocial health.